EXPLORING TEACHERS` STRATEGIES IN IMPLEMENTING COMMUNICATIVE LANGUAGE TEACHING IN TEACHING SPEAKING - Syifa Azzahra, Nazara; Srisudarso, Mansyur; Kartini, Dedeh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Speaking is one of the most important skills in English language learning because it is the main means of communication. However, many students still struggle to use English actively because of limited opportunities to practice communication in the classroom. Therefore, this study aims to explore the teachers’ strategies in implementing Communicative Language Teaching (CLT) in teaching speaking. This research was conducted because research on teachers’ strategies in implementing CLT in teaching speaking at the junior high school level in Indonesia is still limited. This research used a qualitative descriptive approach and involved an English teacher at a junior high school in Karawang. Data were collected through classroom observations and semi-structured interviews, then analyzed using Miles and Huberman’s interactive analysis model, which includes data reduction, data presentation, and the drawing and conclusions. The results of the research indicate that teachers employed six main strategies: facilitating classroom interaction, encouraging student participation, creating a communicative learning environment, organizing communicative learning activities, providing feedback, and managing speaking activities. The most frequently used activities were pair work and paired dialogues. This research also identified several challenges, such as low student self-confidence, limited class time, and large class sizes. The findings suggest that the implementation of CLT can increase student engagement and provide more opportunities to develop English speaking ability.